Analisis Kemampuan Komunikasi Matematis Siswa Kelas VIII SMP pada Materi Sistem Persamaan Linear Dua Variabel - Setyaningsih, Ayu Putri; Hidayati, Nita (Peneliti.net, 2024)
Communication skills are one of the five standard abilities that students must have. Mathematical communication skills play an important role in learning, such as in solving problems and communicating solutions in various daily activities. The necessity of having these abilities makes researchers aim to analyze the mathematical communication skills of class VIII SMP students on the material Systems of Linear Equations in Two Variables. The research method used in this research is descriptive research with a qualitative approach. The selection of subjects in this research was carried out by purposive sampling at one of the junior high schools in Karawang, namely class VIII of SMP Negeri 1 Kotabaru. The types of instruments in this research were tests of mathematical communication skills, and interviews aimed at selected subjects, namely students in the high, medium and low categories. The results of this research show that the communication skills of class VIII students at SMP Negeri 1 Kotabaru on the material Systems of Linear Equations in Two Variables are in the medium category (47.1%) with an average score of 41.75.